Efficacy of laser myringotomy compared with incisional myringotomy for the treatment of otitis media with effusion in pediatric patients: A systematic review. (August 2019) - Zong, Shimin; Wen, Yingying; Guan, Yexiao; Liu, Tianyi; Luo, Pan; Qu, Yanji; Du, Peiyu; Chen, Pei; Xiao, Hongjun
Abstract: Background: Recent reports have shown that laser myringotomy (LM) is increasingly used to treat otitis media with effusion (OME), with higher effectiveness, fewer complications, and lower recurrence rate. Objective: A systematic review of the published literature was conducted to assess the efficacy of LM compared with incisional myringotomy (IM) with or without tympanostomy ventilation tube (VT) for the surgical treatment of OME in pediatric patients (age ≤ 18 years). Methods: We searched the PubMed, Web of Science, Ovid, VIP Chinese, China National Knowledge Infrastructure (CNKI), and Wanfang Chinese databases for articles published before Nov 20, 2018. All relevant articles were reviewed and selectively collected according to inclusion and exclusion criteria. The quality of the included studies was assessed. The data in the eligible studies were extracted and analyzed. Results: A total of 8 studies, including 698 patients and 1262 ears, were included. The types of studies examined include randomized controlled trials (RCTs) and case-control studies of varying quality. The outcomes and complications of LM and IM with or without VT were charted and compared. No quantitative meta-analysis could be performed. Conclusions: LM, characterized by much higher recurrence of OME and less complications, is less effective than IM+VT in keeping the middle ear ventilated and relieving middle ear effusion, but more effective than IM alone. The different interventions seem to show no significant differences in hearing improvement. Nevertheless, additional high-quality research is needed to perform more advanced analyses and to confirm and update our results and conclusions.